Salen, salan and salalen zinc(ii) complexes in the interaction with HS−: time-resolved fluorescence applications. Issue 5 (12th January 2023) - Strianese, Maria; D'Auria, Gerard Joseph; Lamberti, Marina; Landi, Alessandro; Peluso, Andrea; Varriale, Antonio; D'Auria, Sabato; Pellecchia, Claudio
Abstract : We studied the reactivity of HS − with a family of zinc complexes. The different fluorescence trends observed for 1 and 3 in the presence of HS − has been related with the possible existence of non-radiative decay paths, by means of a DFT-analysis. Abstract : In the current work we investigate the route of interaction of a newly synthesized family of zinc complexes with HS − by a plethora of different spectroscopic techniques. A computational analysis on the time dependent density functional theory (TD-DFT) level explored the overall fluorescence properties of the title complexes and their different fluorescence responses to HS − . Time-resolved fluorescence experiments were also performed and highlight the great potential of the current systems to be implemented as HS − fluorescent sensors.